The deposit policy of commercial banks in Uzbekistan and the factors for enhancing its effectiveness - Komilova Mukammal Shavkatovna (International Journal of Accounting and Management Information Systems, 2025)
Purpose: This study aims to examine the deposit policy of commercial banks in Uzbekistan within the framework of the 2020–2025 banking system reform strategy. It seeks to identify the key factors influencing deposit volumes, assess the effectiveness of current policies, and provide recommendations for strengthening deposit mobilization in line with international benchmarks. Research methodology: The research employed a mixed-methods approach, including statistical analysis of deposit shares in banks’ liabilities, comparative analysis with developed countries, theoretical review of deposit policy frameworks, and empirical illustrations from leading commercial banks such as TBC Bank, Xalq Bank, and InFinBank. Results: The findings show fluctuations in the share of deposits in liabilities, from 45.05% in 2020 to 37.2% in 2021, recovering to 45.4% in 2023 before slightly declining in 2024. Interest rate policies, ranging from 19% to 27%, flexibility of terms, and the level of public trust were identified as the most significant factors influencing deposit growth. Comparisons indicate that Uzbekistan still lags behind developed countries, where deposits account for 60–70% of liabilities. Conclusions: Effective deposit policy needs fair rates, transparency, financial literacy, digital banking, deposit insurance, state-bank reforms, and customer focus.. Limitations: The study’s 2020–2025 Uzbekistan scope and reliance on secondary data limit broader generalization and depth of behavioral insights. Contribution: This research contributes to banking policy studies by highlighting the strategic role of deposit mobilization in financial stability and providing practical recommendations to enhance competitiveness and trust in Uzbekistan’s banking sector.